2018
DOI: 10.3389/fgene.2018.00681
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Studies in a Large Cohort of Hearing Impaired Italian Patients Revealed Several New Alleles, a Rare Case of Uniparental Disomy (UPD) and the Importance to Search for Copy Number Variations

Abstract: Hereditary hearing loss (HHL) is a common disorder characterized by a huge genetic heterogeneity. The definition of a correct molecular diagnosis is essential for proper genetic counseling, recurrence risk estimation, and therapeutic options. From 20 to 40% of patients carry mutations in GJB2 gene, thus, in more than half of cases it is necessary to look for causative variants in the other genes so far identified (~100). In this light, the use of next-generation sequencing technologies has proved to be the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…On the other hand, no deletions in GJB6 have been detected, and the A1555G mitochondrial mutation. These results, combined with the outcomes of the previous works [ 10 , 52 ] suggest that GJB6 and MT-RNR1 are not a common cause of NSHL in the Italian population, despite their relevant role in other areas of the world.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…On the other hand, no deletions in GJB6 have been detected, and the A1555G mitochondrial mutation. These results, combined with the outcomes of the previous works [ 10 , 52 ] suggest that GJB6 and MT-RNR1 are not a common cause of NSHL in the Italian population, despite their relevant role in other areas of the world.…”
Section: Discussionsupporting
confidence: 66%
“…The implementation of next-generation sequencing technologies (NGS), together with molecular karyotyping (e.g., Single Nucleotide Polymorphism (SNP) array or Comparative Genomic Hybridization (CGH) array) and other validating assays (e.g., Multiplex Ligation Probe Amplification—MLPA), has dramatically increased the diagnostic rate of HHL, leading to the identification of several mutations and Copy Number Variations (CNVs) in known deafness genes, as well as to the discovery of new disease genes [ 10 , 11 , 12 , 13 ]. The possibility to simultaneously screen large number of genes is essential to address with the genetic heterogeneity of HHL.…”
Section: Introductionmentioning
confidence: 99%
“…Few previous reports have discussed the prevalence of the LOXHD1 gene amongst SNHL patients. In relatively large cohorts that evaluated more than 100 patients, the prevalence of this gene was estimated to 0.71% in American SNHL patients (8/1119), 1.5% in the Netherlands (3/200) and 0.97% in Italy (1/103) [19,22,28]. This result is similar with our study in the American patients, but noticeably higher in the other two countries.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we identified 28 individuals with LOXHD1 variants including 13 novel variants by MPS screening. A total of 44 LOXHD1 variants have been reported to date from various countries, and this study is the largest analysis of LOXHD1 -related HL yet (Table 3) [5,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. Among the identified variants, 11 were non-truncating variations (52.4%) and 10 were truncating variations (47.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in 2013, Roosing et al described maternal UPD of chromosome 6, which included a pathogenic TULP1 variant responsible for the cone dystrophy phenotype of the proband. For HL, several cases of UPD have been described as well, affecting chromosome 1 ( USH2A ) [ 183 ], chromosome 13 ( GJB2) [ 182 ], and chromosome 18 ( LOXHD1 ) [ 182 , 184 ].…”
Section: Variant Interpretationmentioning
confidence: 99%